2021
DOI: 10.1002/chem.202005087
|View full text |Cite
|
Sign up to set email alerts
|

How the Physicochemical Properties of the Bulk Material Affect the Ablation Crater Profile, Mass Balance, and Bubble Dynamics During Single‐Pulse, Nanosecond Laser Ablation in Water

Abstract: Understanding the key steps that drive the laser‐based synthesis of colloids is a prerequisite for learning how to optimize the ablation process in terms of nanoparticle output and functional design of the nanomaterials. Even though many studies focus on cavitation bubble formation using single‐pulse ablation conditions, the ablation efficiency and nanoparticle properties are typically investigated under prolonged ablation conditions with repetition rate lasers. Linking single‐pulse and multiple‐pulse ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 110 publications
(319 reference statements)
0
10
0
Order By: Relevance
“…[104] This was previously reported by Kalus et al who found higher gas and hydrogen formation rates in water when using higher fluences. [105] However, correlations between gas formation and laser parameters in organic solvents have rarely been addressed so far. LAL of Au in n-hexane was performed at two different lasers and the results are shown in Table S3.…”
Section: Influence Of Laser Fluencementioning
confidence: 99%
“…[104] This was previously reported by Kalus et al who found higher gas and hydrogen formation rates in water when using higher fluences. [105] However, correlations between gas formation and laser parameters in organic solvents have rarely been addressed so far. LAL of Au in n-hexane was performed at two different lasers and the results are shown in Table S3.…”
Section: Influence Of Laser Fluencementioning
confidence: 99%
“…For ns-LAL the reflectivity change in water is more pronounced than in air due to supercritical water layer formation and an emerging vapor layer 26 . The time scale of the supercritical water layer formation is dependent on the laser fluence.…”
Section: Discussionmentioning
confidence: 97%
“…Following the observation of Starinskiy et al 26 , it is hypothesized that for pulse durations of several hundred ps to 1 ns, the laser pulse is shorter than the starting time for vapor layer formation. Thus, this loss mechanism can be excluded for 3 ps pulses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations